Construction & Demolition Waste Recycling Problem and Evaluation of the Situation in Turkey in Terms of Legislation - Ceyda Buzkan; Onur Erman (Doğal Afetler ve Çevre Dergisi)
Wastes resulting from the accelerated construction activity with the increasing population are defined as construction and demolition (C&D) waste. C&D wastes that cause environmental problems of various sizes should be recycled to reduce the consumption of natural resources and to use them efficiently. Recycling of waste is known to be effective in terms of sustainable environmental quality, conservation of natural resources as well as social and economic prosperity. Some countries have developed legislation and practices, with the aim of adaptation of the sustainability concept, which was mentioned for the first time in World Commission on Environment and Development Report, into the construction sector. In our country, although legal regulations in this scope are in force, no recycling data can be provided at the desired value. The regulation on the recycling of C&D wastes that came into force in 2004 is already in practice; nevertheless, it is considered that the practices and arrangements for the promotion of recycling and the protection of the environment are insufficient. It has been tried to evaluate the situation in our country in terms of legislation by touching on the C&D waste problem that emerged as a result of the rapidly increasing construction activities in recent years. Within the scope of the study, the EU and other developed countries, and the legislation in our country are being examined and the requirements for implementation are stated.